Tumor Necrosis Factor Alpha Mediates GABAA Receptor Trafficking to the Plasma Membrane of Spinal Cord Neurons In Vivo - Ellen D. Stück; Randolph N. Christensen; J. Russell Huie; C. Amy Tovar; Brandon A. Miller; Yvette S. Nout; Jacqueline C. Bresnahan; Michael S. Beattie; Adam R. Ferguson (Neural Plasticity)
The proinflammatory cytokine TNFα contributes to cell death in central nervous system (CNS) disorders by altering synaptic neurotransmission. TNFα contributes to excitotoxicity by increasing GluA2-lacking AMPA receptor (AMPAR) trafficking to the neuronal plasma membrane. In vitro, increased AMPAR on the neuronal surface after TNFα exposure is associated with a rapid internalization of GABAA receptors (GABAARs), suggesting complex timing and dose dependency of the CNS’s response to TNFα. However, the effect of TNFα on GABAAR trafficking in vivo remains unclear. We assessed the effect of TNFα nanoinjection on rapid GABAAR changes in rats (𝑁=30) using subcellular fractionation, quantitative western blotting, and confocal microscopy. GABAAR protein levels in membrane fractions of TNFα and vehicle-treated subjects were not significantly different by Western Blot, yet high-resolution quantitative confocal imaging revealed that TNFα induces GABAAR trafficking to synapses in a dose-dependent manner by 60 min. TNFα-mediated GABAAR trafficking represents a novel target for CNS excitotoxicity.